Analysis of Factors That Influence Consumers in Shopping for Fresh Vegetables in Traditional Markets in Jambi City - Nainggolan , Saidin; Saffudin, Nanang; Nainggolan, Viona (Randwick International of Social Science Journal, 2025)
This study aims to analyze the factors influencing consumer behavior in purchasing fresh vegetables in traditional markets in Jambi City. This study was conducted in traditional markets in Jambi City. The research location was selected using a purposive sampling method. Data analysis used in this study utilized primary data and a descriptive approach.Partial Least Square - Structural Equation Model (PLS-SEM). The results of the study show 1) Based on Age, it shows that most consumers are aged >36 years as much as (45%), priority shopping places in traditional markets as much as (100%), Consumers consider consuming vegetables very important as much as (76.66%), consumers consume fresh vegetables as Fulfilling nutritional needs (90%), wives are the decision makers for shopping for vegetables in traditional markets as much as (80%), consumers decide to shop for fresh vegetables in traditional markets in a planned manner as much as (91.66%), The frequency of consumers shopping for fresh vegetables in traditional markets is twice a week as much as (60%), the types of vegetables that are often consumed are types of fruit vegetables as much as (90%). 2). Internal factors with manifest variables of education level, occupation, and income level have a positive and significant effect on consumer behavior. External factors with manifest variables of community habits, family, environment, and location have a positive and significant effect on consumer behavior, while internal factors with moderating variables of consumer perception have a positive but not significant effect on consumer behavior. Likewise, external factors with moderating variables of consumer perception have a positive but not significant effect on consumer behavior.